Creative and sensitive production of care-educational technology for families of children with gastrostomy - Ana Caroline Silva Caldas; Rosilda Silva Dias; Santana de Maria Alves de Sousa; Elizabeth Teixeira (Escola Anna Nery, 2019)
Abstract Objective: To describe the production process of a care-educational technology for families of children with gastrostomy based on the models of Hildegard Peplau and Paulo Freire. Method: Descriptive and qualitative research, carried out from October 2016 to February 2017 in three health units and a residential unit in São Luís, MA, Brazil. Thirteen family members participated. Were used from the creative method sensitive to dynamic body knowledge, semi-structured interview and observation. Thematic analysis. Results: From the problem situations that emerged from the corpus, the contents of the technology were constructed, and decoding in subtopics. The technology is of the printed type (booklet), titled The child and his gastrostomy: a guide for families and caregivers. Contains 24 pages and nine content topics, with texts and images. Conclusion: Social evidence that favored the production of a technology that is sensitive to reality, which, after being validated, will help families emerged. Implications for practice: The booklet can be used in the teaching and assistance activities of the families.